2001
DOI: 10.1046/j.1440-1746.2001.02512.x
|View full text |Cite
|
Sign up to set email alerts
|

Laterally spreading tumor: Clinicopathological study in comparison with the depressed type of colorectal tumor

Abstract: It seems appropriate that these LSTs with depression should be distinguished from depressed-type colorectal tumors and regarded as constituting a new clinical entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…It has a tendency to affect the rectum, sigmoid colon, and caecum. In some studies, it has been reported that the carcinogenesis rate of LST is 8.64%-52.5% [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has a tendency to affect the rectum, sigmoid colon, and caecum. In some studies, it has been reported that the carcinogenesis rate of LST is 8.64%-52.5% [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…It has a tendency to affect the rectum, sigmoid colon, and caecum. In some studies, it has been reported that the carcinogenesis rate of LST is 8.64%-52.5% [13][14][15] . Abstract AIM: To study the molecular mechanism of laterally spreading tumor (LST), a cell line [Laterally Spreading Tumor-Rectum 1 (LST-R1)] was derived and the characteristics of this cell line were investigated.…”
mentioning
confidence: 99%
“…1). [1][2][3][4][5] All patients underwent preoperative colonoscopy with biopsy of the tumor and colonoscopic ultrasonography. Metallic clips were placed as markers by preoperative colonoscopy.…”
Section: Laterally Spreading Tumors (Lsts)mentioning
confidence: 99%
“…Colectomy with regional lymph node dissection was performed for tumors considered to have submucosal invasion on the basis of endoscopic findings. 4,5 All steps of the minilaparotomy approach were done using conventional surgical techniques and instruments via a small abdominal incision no longer than 7 cm. 14 The surgical technique used to perform limited colectomy or colectomy with regional lymph node dissection through a minilaparotomy was previously described.…”
Section: Operative Technique Of the Minilaparotomy Approachmentioning
confidence: 99%
See 1 more Smart Citation